2021
DOI: 10.21608/ajfm.2021.139285
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of N-acetylecysteine on cyclosporine induced testicular toxicity in male albino rats

Abstract: Introduction: Cyclosporine A (CsA) is considered one of the potent drugs that are used extensively in organ transplant and oncology patients. It is also used in autoimmune diseases. Unfortunately, its use is accompanied with several hazards; one of these is testicular toxicity. Nacetylecysteine (NAC) is an antioxidant found to reduce CsA toxicity. Aim of the work: The study aims to determine the toxic effect of exposure to cyclosporine on the testis and to investigate the protective role of NAC. Methods: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The decrease in the luteinizing hormone could also be a result of a decreased expression of the Leydig cell. The decrease in the follicle stimulating and testosterone in this study is in agreement with a study conducted by Pan et al (2018) and Abdelkader et al (2021). These hormones play a crucial role in spermatogenesis and a decrease will affect the sperm motility, viability, morphology, and also affect the testis's weight.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease in the luteinizing hormone could also be a result of a decreased expression of the Leydig cell. The decrease in the follicle stimulating and testosterone in this study is in agreement with a study conducted by Pan et al (2018) and Abdelkader et al (2021). These hormones play a crucial role in spermatogenesis and a decrease will affect the sperm motility, viability, morphology, and also affect the testis's weight.…”
Section: Discussionsupporting
confidence: 93%
“…An alteration in this axis will affect the secretion of the follicle‐stimulating hormone, luteinizing hormone, and testosterone. Various studies have shown that the use of cyclosporine has a suppressive effect on the hormonal–pituitary gonadal axis in animal studies (Abdelkader et al, 2021). The use of cyclosporine decreases the level of serum testosterone by affecting the biosynthesis and secretion of testosterone in the testes.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine A is a cyclic polypeptide drug with strong immunosuppressive potency [1]. Cyclosporine has been widely used in transplantation and preventing organ rejection, as well as in treating autoimmune diseases [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high toxicity, Cyclosporine A administration can be accompanied by many adverse side effects such as the nephrotoxic, hepatotoxic, neurotoxic and testicular toxicity [1][2][3][4]. cyclosporine toxicity on fertility and other side effects limit its clinical use [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%